Methods in alcohol-related neuroscience research - Liu, Yuan; Ed. Lovinger, David M; Ed (Methods & new frontiers in neuroscience, 2002)
Offers an overview of the many areas in investigating the effects of alcohol on the brain. This book provides technical guidance for investigators doing research at the molecular, cellular, systems, and behavioral levels.